Keanekaragaman Jenis Kupu-kupu di Taman Nasional Karimunjawa Jawa Tengah: Diversity of butterflies in Karimunjawa National Park of Central Java - Wisnu Bayu MURTI; Nugroho Edi KARTIJONO; Margareta RAHAYUNINGSIH (Universitas Jambi, 2017)
Karimunjawa National Park has several types of ecosystems that hold high biodiversity potential and have not been fully recorded. Karimunjawa National Park is the habitat of flora and fauna including butterflies there. The objective of the research was the diversity of butterfly species in Karimunjawa Island. The study was conducted on August-September 2017. The method of the research using Point Count method. Data analysis using diversity index, evenness index, dominance index, and similarity index. The results showed that the index of diversity (H') of butterfly community on Karimunjawa Island has value (2.95), it indicates that the condition of the butterfly community is stable. The result of the Eveness Index obtained a high yield E = 0.76, it shows that the individual distribution of each type of butterfly on Karimunjawa Island is evenly distributed. The result of the dominant Index shows a low value (0.10), thus no dominance is concentrated on a particular type of butterfly. Analysis of similarity index of species in all habitats observed obtained results IS= 53-73%, this shows that in the three habitats observed can be inhabited by almost all butterfly species and Has an equally important role as a community of butterflies in Karimunjawa Island. Keywords: biodiversity, butterfly, Karimunjawa Island